Development strategy business of Sipirok weaving handicrafts - Muhammad Buchari Sibuea; Faiz Ahmad Sibuea (Proceedings of AICS - Social Sciences, 2017)
Woven craft business is an effort to preserve the culture of Indonesia and as a livelihood for some people where one of the very specific is Tenun Sipirok. But because of the lack of optimal development, it is feared will affect the prospects in the future. The purpose of this research is to know (1) income level of entrepreneur, (2) influence of internal and external environment condition to business development and (3) business development strategy. This research is descriptive conducted in District of South Tapanuli with interview method and purposive sample determination. The results showed that Sipirok Tenun business is profitable where the income Rp.54,000,000 and average production cost Rp.37,969,167 so that average income Rp.16,030,833 every month. Through SWOT analysis, the matrix value of internal factor is 2.658 and external factor is 2.650. This position belongs to the category of applying an aggressive strategy that means being in a very favorable situation or having opportunities and strength. The strategy that must be implemented is to take advantage of opportunities for profit. The study recommends employers to improve their employees' skills through training, additional capital to hire reliable employees in order to keep up with consumer demand, better management in terms of time, finances, raw material stock and better marketing effectively to be independent of certain traders. It is expected that the government will make effective training and the need for traditional markets specifically for the sale of results.